2017
DOI: 10.1097/bor.0000000000000411
|View full text |Cite
|
Sign up to set email alerts
|

Genetic advances in systemic lupus erythematosus: an update

Abstract: Purpose of review -More than 80 loci are now reported to show robust genetic association with Systemic Lupus Erythematosus (SLE). The differential functional effects of the risk alleles for the majority of these loci remain to be defined. Here, we review current SLE association findings and the recent progress in the annotation of non-coding regions of the human genome as well as the new technologies and statistical methods that can be applied to further the understanding of SLE genetics.Recent findings -Genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 65 publications
1
90
0
1
Order By: Relevance
“… Illustration of genetic overlap between four musculoskeletal immune‐mediated inflammatory diseases (IMIDs), showing number of gene regions associated across two or more conditions, with gene names listed .…”
Section: Genetic Sharing Between Musculoskeletal Imidsmentioning
confidence: 99%
“… Illustration of genetic overlap between four musculoskeletal immune‐mediated inflammatory diseases (IMIDs), showing number of gene regions associated across two or more conditions, with gene names listed .…”
Section: Genetic Sharing Between Musculoskeletal Imidsmentioning
confidence: 99%
“…Transfer of human autoantibodies from patients with SLE can cause glomerulonephritis and proteinuria in murine experimental systems,18, 19 emphasizing that they can be pathogenic. Genome‐wide association studies (GWAS) have shown that over 80 loci can contribute to the risk of developing SLE 20. The pathogenesis of the disease is complex, but several broad themes emerge.…”
Section: Slementioning
confidence: 99%
“…Genome-wide association studies (GWAS) have shown that over 80 loci can contribute to the risk of developing SLE. 20 The pathogenesis of the disease is complex, but several broad themes emerge. Multiple genes involved in: (i) the clearance of immune complexes and apoptotic cells; (ii) the regulation of innate immunity, such as the type 1 interferon and complement pathways; and (iii) the regulation of lymphocyte activation and function have been implicated.…”
Section: Slementioning
confidence: 99%
“…Genome-wide association studies (GWAS) have been successfully used to investigate the genetic basis of a disease and this has dramatically advanced knowledge of the genetic aetiology of SLE. Our recent review summarized a total of 84 genetic loci that are implicated as SLE risk (11). Despite the advances in the genetics of SLE, it is not clear how to utilise genetic information for the prediction of SLE risk or severity.…”
Section: Introductionmentioning
confidence: 99%